2017
DOI: 10.1136/postgradmedj-2017-135035
|View full text |Cite|
|
Sign up to set email alerts
|

Medical research and audit skills training for undergraduates: an international analysis and student-focused needs assessment

Abstract: Nearly one-third of students lacked formal training on undertaking research, and half of students lacked formal audit training and opportunities to undertake audit as part of their medical school course. The presence of research training in the cirriculum was associated with an increase in perceived opportunities to participate in MEDINE2 research competencies. Female gender and a lack of previous research experience were significant factors influencing confidence and participation in research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…Validated questionnaires were not found for the surveys; however, modified versions of previous questionnaires were found which enabled a comparison to be made to previous studies [ 25 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Validated questionnaires were not found for the surveys; however, modified versions of previous questionnaires were found which enabled a comparison to be made to previous studies [ 25 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…A pre- and post-study questionnaire was adapted with permission from the STARSurg 2015 initiative/MEDINE 2 consensus survey of research competencies [ 25 , 30 ]. The Medical Education in Europe (MEDINE) Thematic Network had previously undertaken a pan-European consensus survey to generate a set of research competencies and core learning outcomes for medical curricula in Europe across all three Bologna cycles (Bachelor, Master and Doctor).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Critical appraisal has recently been identified by UK final year medical students as the most important research competency to obtain and is essential for student engagement with academic medicine 6. It is imperative that doctors are able to critically appraise and evaluate research in order to provide better patient care.…”
Section: Discussionmentioning
confidence: 99%
“…Despite this, previous studies have shown that medical students in the UK have limited confidence with critical appraisal, and have little opportunity to participate 68. This has been attributed to factors such as restricted time for critical appraisal teaching within the curriculum,9 lack of previous research experience,6 and inability to take part in an intercalated degree 10…”
Section: Introductionmentioning
confidence: 99%